A Comparison between STAAD.Pro and Tekla Structure Software for RC Design and Analysis - Asri, Mohamad Hanif Najmie; Khalil, Khairil Aidid; Airul Azhar, Nur Syamimie; Kesot, Mohd Jahaya (Multidisciplinary Applied Research and Innovation, 2023)
The purpose of this project is to conduct an in-depth investigation of the major features of two commonly used structural analysis and design software programmes, STAAD.Pro and Tekla Structure software. Each software application has its own set of features, analysis options, design and output options, as well as limitations, and benefits. To avoid failure, it is necessary for the user to exploit all of  the advantageous features of a specific software programme. To complete the design and analysis, the geometry has been set before and the materials used to design and analyse the geometry are Columns, Beams and Slabs by using predefined specifications. As a result, STAAD.Pro and Tekla Structure can run and analysis the geometry predefined and produce different output result and data. The data analysis from both softwares show a minor differentiation of unit accuracy and STAAD.Pro has advance features to set up rather than Tekla Structure but Tekla Structure produce easily mainframe for a beginner user.